Ruminal Acidosis in Feedlot: From Aetiology to Prevention - Joaquín Hernández; José Luis Benedito; Angel Abuelo; Cristina Castillo (The Scientific World Journal)
Acute ruminal acidosis is a metabolic status defined by decreased blood pH and bicarbonate, caused by overproduction of ruminal D-lactate. It will appear when animals ingest excessive amount of nonstructural carbohydrates with low neutral detergent fiber. Animals will show ruminal hypotony/atony with hydrorumen and a typical parakeratosis-rumenitis liver abscess complex, associated with a plethora of systemic manifestations such as diarrhea and dehydration, liver abscesses, infections of the lung, the heart, and/or the kidney, and laminitis, as well as neurologic symptoms due to both cerebrocortical necrosis and the direct effect of D-lactate on neurons. In feedlots, warning signs include decrease in chewing activity, weight, and dry matter intake and increase in laminitis and diarrhea prevalence. The prognosis is quite variable. Treatment will be based on the control of systemic acidosis and dehydration. Prevention is the most important tool and will require normalization of ruminal pH and microbiota. Appropriate feeding strategies are essential and involve changing the dietary composition to increase neutral detergent fiber content and greater particle size and length. Appropriate grain processing can control the fermentation rate while additives such as prebiotics or probiotics can help to stabilize the ruminal environment. Immunization against producers of D-lactate is being explored.